Talleres de adultos mayores: un aporte para el envejecimiento activo - Ganso, Héctor (2012)
Workshops on aging: a contribution to active aging - SynopsisThere is a global silent revolution that places the elderly as its protagonist; the population shift demands its treatment as a social economic problem transcendental to the twenty first century. Active aging positions itself as a strategic weapon to face said problem. The aim of this study is to present the various workshops for elderly persons who are held at the National University of Quilmes, the only ones that are offered for different age. Its origin, operation and aiming to achieve purposes. The aim is to help the elderly achieve better quality of live, revalue and positively accept the fact of growing old. Facilitate the access to cultural available resources. Evaluate the human capital of the elderly person and consider him as a socially active component. Growing old is a personal and collective achievement in society.